Presence of Helicobacter pylori in drinking water of Karachi, Pakistan - Khan, Adnan; Farooqui, Amber; Kazmi, Shahana Urooj (The Journal of Infection in Developing Countries, 2011)
Background: Prevalence of Helicobacter pylori (H. pylori) infection is an increasing problem in developing countries. Several environmental factors such as overcrowding, poverty, contaminated drinking water and food are considered to contribute toward transmission of infection; however, little is known about their definitive roles. The aim of this study is to investigate the presence of H. pylori in drinking water samples of Karachi, Pakistan. Methodology: Samples of drinking water were collected from 18 different towns located in the metropolitan area of Karachi. Samples were concentrated by membrane filtration method and subjected to PCR for the detection of H. pylori. Results: Two out of 50 (4%) samples collected from two different densely populated town areas were found to be positive for H. pylori. Conclusion: The study provides evidence for the presence of H. pylori in municipal drinking water of Karachi.